2021
DOI: 10.1002/ctm2.592
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α promotes tumour growth in clear cell renal cell carcinoma by increasing the expression of NUDT1 to reduce oxidative stress

Abstract: BackgroundThe key role of hypoxia‐inducible factor 2alpha (HIF2α) in the process of renal cancer has been confirmed. In the field of tumour research, oxidative stress is also considered to be an important influencing factor. However, the relationship and biological benefits of oxidative stress and HIF2α in ccRCC remain unclear. This research attempts to explore the effect of oxidative stress on the cancer‐promoting effect of HIF2α in ccRCC and reveal its mechanism of action.MethodsThe bioinformatics analysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Previous studies indicated that NUDT1 might provide diagnostic and prognostic value for KIRC [ 44 ]. A study revealed that NUDT1 is activated by HIF2 α transcription, thereby inhibiting oxidative stress and promoting the progression of ccRCC [ 45 ]. The roles of NUDT4 and NUDT10 remain ambiguous in ccRCC tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that NUDT1 might provide diagnostic and prognostic value for KIRC [ 44 ]. A study revealed that NUDT1 is activated by HIF2 α transcription, thereby inhibiting oxidative stress and promoting the progression of ccRCC [ 45 ]. The roles of NUDT4 and NUDT10 remain ambiguous in ccRCC tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HIF-2α was associated with higher ferroptosis susceptibility in colorectal cancer cells, in murine colon tumors [51] and clear cell carcinoma cells [52] by regulation of cellular lipid and iron metabolism. However, HIF-2 signaling was also reported to reduce oxidative stress by inducing the transcription of nucleoside diphosphate-linked moiety X-type motif 1 in clear cell renal cell carcinoma, which promoted tumor growth [53]. HIF-1α, on the other hand, was attributed a protective effect against ferroptosis in several cancer cells by reducing iron and ROS levels [54], promoting lipid storage and regulating lipid metabolism [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…One typical feature of cancers is the capability to equilibrate the increased oxidative stress with high antioxidant levels [29]. As a transcription factor, Nrf2 is an essential stress response mediator, for which KEAP1 acts as a negative regulator [30].…”
Section: Discussionmentioning
confidence: 99%